Pengaruh Budaya Organisasi dan Kepuasan Kerja Terhadap Disiplin Kerja Karyawan Bagian Produksi di PT XYZ Kabupaten Bandung Barat - Hasna Rohaeni Fauziyah; RM Juddy Prabowo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Human resources are an important factor in the success of an organization. PT XYZ is a textile company engaged in the dyeing and finishing of textile materials. Based on the data, there is an increase in the percentage of absenteeism and employee turnover from year to year, which is suspected to be caused by job dissatisfaction and is an indication of work indiscipline. This study aims to determine the influence of organizational culture and job satisfaction on employee work discipline in the Production Department of PT XYZ, West Bandung Regency. The method used is a quantitative method with a multiple regression analysis approach and a coefficient of determination using SPSS version 25. The data collection technique was carried out by distributing questionnaires to 107 respondents. The results of the study indicate that: (1) organizational culture has a positive effect on employee work discipline; (2) job satisfaction has a positive effect on employee work discipline; and (3) Organizational culture and job satisfaction have a significant influence on employee work discipline.. These findings indicate that the transformation of organizational culture and job satisfaction can be a strategic effort to improve employee work discipline.